DETERMINAN LABA BERSIH DENGAN EKUITAS SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR - Sastrawan, Rahman; Saputra, Edi; Toliang, Ermina (JURNAL LENTERA AKUNTANSI, 2023)
The main purpose of establishing a company is to make a profit, so that the business continues to grow. Factors that influence a company's net profit are sales, production costs, operational costs and income taxes. The aim of this research is to see how much influence sales, production costs, operational costs, income taxes have on net profit: equity as moderation (Study of Companies Listed on the Indonesian Stock Exchange for the 2019-2022 period). The population of this research is manufacturing companies operating in the food and beverage sub sector which are listed on the Indonesian Stock Exchange. The sampling technique uses purposive sampling with the level of clarity (explanation) method. The data used in this research is secondary data in the form of financial reports of food and beverage sector manufacturing companies for 2019-2022. The analysis method for hypothesis testing uses the Eviews application using a panel data regression model. The research results show that sales, production costs and operational costs have no effect on the company's net profit and equity cannot moderate it, while income tax has a significant effect on net profit and the company's equity cannot moderate it. Keywords: Sales, Production Costs, Operational Costs, Income Tax, Net Profit